Prenatal sex selection and girls' well-being: Evidence from India - Luojia Hu; Analia Schlosser (Institute for the Study of Labor (IZA), 2011)
In this paper, we study the impact of prenatal sex selection on the well-being of girls by analyzing changes in children's nutritional status and mortality during the years since the diffusion of prenatal sex determination technologies in India. We further examine various channels through which prenatal sex selection might affect girls' outcomes. Using repeated cross-sections from a rich survey dataset, we show that high sex ratios at birth reflect the practice of sex selective abortion. We then exploit the large regional and time variations in the incidence of prenatal sex selection to analyze whether changes in girls' outcomes relative to boys within states and over time are associated with changes in sex ratios at birth. We find that an increase in the practice of prenatal sex selection appears to be associated with a reduction in the incidence of malnutrition among girls. The negative association is stronger for girls born in rural households and at higher birth parities. An examination of the various mechanisms linking between prenatal sex selection and children outcomes suggests that prenatal sex selection does not lead to a selection of girls into better endowed families, but there is some evidence of a larger reduction in family size for girls relative to boys. We also find an increase in girls' breastfeeding duration suggesting an improvement in parental care and treatment. On the other hand, prenatal sex selection does not appear to be associated with a reduction in excess female child mortality, or a reduction in son preference.
urn:nbn:de:101:1-201104133844
Keywords: J13; J16; I1; O12; 330; son preference; prenatal sex selection; ultrasound; sex ratio at birth; gender discrimination; child health; Schwangerschaftsabbruch; Geschlechterdiskriminierung; Kinder; Frauen; Gesundheit; Indien